Leadership Challenges in a South African Sector Education and Training Authority (SETA) - Mudau, Fhatuwani (University of the Witwatersrand, Johannesburg, 2025)
Since the dawn of democracy in 1994, South Africa has realised significant changes across different spectrums, with leadership being one of those. Nelson Mandela became the first leader to be democratically elected as president of the Republic South Africa and led the entire nation irrespective of gender, race, ethnic group, and socio-economic status. Leadership is a highly complex topics as it has many dynamic challenges and opportunities. This research study assesses the leadership challenges in a South African Sector Education and Training Authority. There are twenty-one (21) Sector Education and Training Authorities (SETAs). Each of these SETAs is designated to facilitate skills development in their respective economic clusters as outlined by the Skills Development Act, No. 97 of 1998 as amended (the Act). The research study explored different leadership theories to assess the leadership challenges in the sector education and training authority, including situational leadership, laissez-faire leadership, servant leadership, democratic leadership, and exemplary leadership. Ultimately, the exemplary leadership resonated with the topic at hand as well as the problem statement and research gap identified. To explore this further, the researcher drew on the framework of Kouzes and Posner (2012) about the Five Practices of Exemplary Leadership. The framework comprises five elements of exemplary leadership, which are model the way, inspire a shared vision, challenge the process, enable others to act, and encourage the heart. These elements of exemplary leadership were examined by developing a measurement instrument to explore the leadership challenges in the sector education and training authority. The measurement instrument together with quantitative methods were utilised as tools to gather data and gain insight into the challenges at hand from 200 sampled employees of the sector ii education and training authority. A non-probability convenience sampling method was utilised. The results revealed that there was a significant relationship between inspiring a shared vision and leadership challenges. Results revealed that there was a significant relationship between encouraging the heart and leadership challenges. The other three hypotheses were insignificant.
A research report submitted in fulfillment of the requirements for the Master of Business Administration, in the Faculty of Commerce Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2025
Keywords: UCTD; Leadership; Encourage; Situational; SDG-4: Quality education; SDG-8: Decent work and economic growth